Rhodium-catalyzed phosphorylation reaction of water-soluble disulfides using hypodiphosphoric acid tetraalkyl esters in water. Issue 23 (6th April 2020) - Arisawa, Mieko; Fukumoto, Kohei; Yamaguchi, Masahiko
Abstract : RhCl3 catalyzed the phosphorylation reaction of water-soluble disulfides, including unprotected glutathione disulfide, with hypodiphosphoric acid tetraalkyl esters in homogeneous water. Abstract : RhCl3 catalyzed the exchange reaction of disulfides and hypodiphosphoric acid tetraalkyl esters in water under homogeneous conditions, which indicated the hypodiphosphoric acid tetraalkyl esters to be novel and efficient phosphorylation reagents in water. The reaction was used in the phosphorylation of unprotected glutathione disulfide.